MINANGKABAU WOMEN IN JAKARTA: THEIR PERCEPTIONS OF THEIR HERITAGE LANGUAGE AND CULTURE - Sukamto, Katharina Endriati; Tyas suci, Eunike Sri (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2018)
Of the so many ethnic groups in Indonesia, the Minangkabau-or Minang-people have the strongest tradition of migration. This ethnic group is also known as the largest matrilineal society in the world (Wikipedia). This qualitative study looks at how the Minang women who live in the surrounding areas of Jakarta perceive the Minang language, Indonesian language, and Minang culture in their daily lives. The data were collected through in-depth interviews with four adult female Minang informants, aged between 39 to 55 years old. This study reveals that the four women no longer perceive the Minang language as important to be maintained. They prefer to use Indonesian in their daily communication, both in the family domain as well as the public domain. In relation to the Minang culture, the four women tend to maintain the egalitarian and democratic principles of the Minang tradition. In fact, the quality of maintaining and passing on the Minang culture to their children depends on the attachment of the women to the culture itself.